Zen in the art of writing - Bradbury, Ray (Santa Barbara : Joshua Odell Editions, 1994)
Contents: The joy of writing. Run fast, stand still or, the thing at the top of the stairs, or, new ghosts from old minds. How to keep and feed a muse. Drunk, and in charge of a bicycle. Investing dimes: fahrenheit 451. Just this side of byzantium: dandelion wine. The long road to mars. On the shoulders of giants. The secret mind. Shooting haiku in a barrel. Zen in the art of writing. On creativity.
Keywords: Creative Ability